Psychological Impact of the COVID-19 Pandemic on Adults and Their Children in Italy - Davico, Chiara; Ghiggia, Ada; Marcotulli, Daniele; Ricci, Federica; Amianto, Federico; Vitiello, Benedetto (Frontiers in Psychiatry, 2021)
Aim: The coronavirus disease 2019 (COVID-19) pandemic has abruptly changed the life of millions as travel and social contacts have been severely restricted. We assessed the psychological impact of COVID-19 on adults and children, with special attention to health care workers (HCWs). Methods: A self-rated online survey, including the Impact of Event Scale-Revised (IES-R) for adults and the Children Revised Impact of Event Scale-Revised-13 items (CRIES-13) for their 8- to 18-year-old offspring, was conducted in Italy on March 20-26, 2020. Linear mixed-effects models were applied to the data, accounting for age, sex, education, and other demographic characteristics. Results: Data were available from 2,419 adults (78.4% females, mean age 38.1 ± SD 13.1 years; 15.7% HCW) and 786 children (50.1% male, mean age 12.3 ± 3.2 years). Median (IQR) IES-R score was 30.0 (21.0-40.0), corresponding to mild psychological impact, with 33.2% reporting severe psychological impact. IES-R was lower in HCWs (29.0) than non-HCWs (31.0), but HCWs directly involved in COVID-19 care had higher scores (33.0 [26.0-43.2]) than uninvolved HCWs (28.0 [19.0-36.0]). Median CRIES-13 score was 21.0 (11.0-32.0), with 30.9 % of the children at high risk for post-traumatic stress disorder. Parent and child scores were correlated. Conclusions: Up to 30% of adult and children in the pandemic area are at high risk for post-traumatic stress disturbances. The risk is greater for HCWs directly involved in COVID-19 care and for their children.